Experiencing the body during pregnancy: A qualitative research study among Spanish sportswomen. Issue 3 (2nd April 2016) - Martinez-Pascual, Beatriz; Abuín-Porras, Vanesa; Pérez-de-Heredia-Torres, Marta; Martínez-Piedrola, Rosa María; Fernández-de-las-Peñas, César; Palacios-Ceña, Domingo
ABSTRACT: The aim of the current qualitative phenomenological study was to describe the body experiences during pregnancy among Spanish elite sportswomen. Twenty Spanish sportswomen with the following criteria were included: (1) aged between 18 and 65 years; (2) had been pregnant during their professional sporting career; and (3) after the end of their pregnancy, had returned to their professional sports career for at least 1 year. A qualitative thematic analysis was conducted. Data were collected from May 2010 to April 2012 using in-depth personal interviews, investigator's field notes, and extracts from the participants' personal letters. Identified themes included: (1) a new body; (2) body control; (3) to feel their bodies and communicate with them; and (4) body's beauty ideal. Understanding the meaning of the body experience for elite Spanish sportswomen might provide us with deeper insight into their expectations and might help in the development of training systems focused on them.